SCHOOL MEDIATION AS A SOCIAL TECHNOLOGY TO FIGHT VIOLENCE AND GUARANTEE RIGHTS TO THE LGBTQIA+ POPULATION - Monteiro Mota, Marcelo José; Lando, Giorge André; Ferreira do Nascimento, Elaine (Revista Inclusiones, 2022)
The present study sought to reflect on the potential of conflict mediation to combat violence and guarantee rights for the LGBTQIA+ population in the school environment. To this end, an extensive bibliographic research was carried out, encompassing scientific production, normative analysis and document consultations, in order to update existing data and carry out a theoretical investigation in order to answer previous questions and those generated during the study. Mediation is a social technology that offers schools and individuals new forms of relationship that strengthen, day by day, a climate of healthy coexistence, by preventing conflict, indiscipline and violence. However, conflicts arising from discrimination and violence based on sexual orientation, gender identity or expression demand a different treatment by the mediator, under penalty of ineffective conflict resolution obtained through school mediation.